Risk map for the water quality of municipal supply systems. A Colombian case (2014)
Meeting the requirements of water quality for human consumption is one of the main challenges faced by companies supplying aqueducts; due to the degradation of the supply sources, the deterioration of the watershed and climate changes threaten the system components. The objective of this paper is to identify, analyze and develop the risk map for the water quality of a Colombian municipal water supply system categorized with a low complexity level. It was realized as a description, analysis and qualitative assessment of the threats and vulnerabilities identified. The risk assessment was carried out through two criteria: (i) estimation of the occurrence probability, and (ii) impact by the risk materialization. The results show that the supply sources “La Moya” and “Bellavista” present dominant risks of the anthropogenic and natural type, respectively. Additionally, the results suggest that the conditions of water quality are suitable for human consumption; however, it is required to ensure the presence of disinfection treatment in the water treatment plant due to the presence of coliforms. Consequently, the water quality risk index shows a classification of “high risk”, mainly due to the presence of coliforms and E. coli.